2019–2020 Florida Citrus Production Guide: Rust Mites, Spider Mites, and Other Phytophagous Mites - Jawwad A. Qureshi; Philip A. Stansly (EDIS)
This 7-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by J. A. Qureshi and P. A. Stansly, and published by the Entomology and Nematology Department, March 2019.